2023
DOI: 10.3390/ani13101666
|View full text |Cite
|
Sign up to set email alerts
|

Application of Blended Learning to Veterinary Gross Anatomy Practical Sessions: Students’ Perceptions of Their Learning Experience and Academic Outcomes

Abstract: The use of blended learning strategies is increasingly common in health sciences, including veterinary medicine; however, there are very few descriptions of these methods being applied to practicals. We describe here the application of blended learning based on the implementation of flipped classrooms with collaborative learning and gamification to the 2020–2021 veterinary medicine gross anatomy practicals at CEU Cardenal Herrera University (Spain). Students prepared for the sessions by pre-viewing videos and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…In contrast, the survey of the following two hybrid semesters showed that lecturers at the TiHo still preferred to use synchronous live events (67.82%) for their teaching, but that the use of asynchronous formats [e.g., instructional videos for practical content (34.49%) and instructional videos on theoretical content (17.24%)], with the exception of assignments with digital delivery (45.98%), was used considerably less ( 20 ). These results are in contrast to the preferred teaching system of a combination of synchronous and asynchronous teaching, which was clearly preferred by teachers at the TiHo in both surveys and should be an indication for further training opportunities, as the use of asynchronous formats in teaching has certainly proven to be successful, as confirmed by the study by Gomez et al, among others ( 28 ). In Naundorf’s study ( 23 ), the majority of lecturers (64.37%) also stated that they had completely reorganized their teaching.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In contrast, the survey of the following two hybrid semesters showed that lecturers at the TiHo still preferred to use synchronous live events (67.82%) for their teaching, but that the use of asynchronous formats [e.g., instructional videos for practical content (34.49%) and instructional videos on theoretical content (17.24%)], with the exception of assignments with digital delivery (45.98%), was used considerably less ( 20 ). These results are in contrast to the preferred teaching system of a combination of synchronous and asynchronous teaching, which was clearly preferred by teachers at the TiHo in both surveys and should be an indication for further training opportunities, as the use of asynchronous formats in teaching has certainly proven to be successful, as confirmed by the study by Gomez et al, among others ( 28 ). In Naundorf’s study ( 23 ), the majority of lecturers (64.37%) also stated that they had completely reorganized their teaching.…”
Section: Discussionmentioning
confidence: 74%
“…Blended learning has many advantages compared to pure face-to-face teaching, not only due to its flexibility in terms of time and space, but also because it enables good interaction between lecturers and learners in asynchronous scenarios and it can reach a large number of students without requiring more teaching resources ( 35 ). Furthermore, it has been shown to increase student engagement, personal responsibility, and satisfaction ( 28 , 36 ). In addition, digital resources are persistent and therefore easy to use over longer periods of time ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation